THE EXISTENCE OF THE LESBIAN, GAY, BISEXUAL AND TRANSGENDER (LGBT) COMMUNITY IN THE PERSPECTIVE OF A STATE BASED ON PANCASILA - I Nyoman Sujana; Komang Arini Setyawati; Ni Made Puspasutari Ujanti (Fakultas Hukum Universitas Gadjah Mada, 2018)
AbstractThe existence of a lesbian, gay, bisexual and transgender community is a necessity. This study aims to understand Pancasila’s view of the existence of Lesbian, Gay, Bisexual, and Transgender (LBGT) communities in Indonesia against the noble values contained in Pancasila and what alternative solutions can be offered in order to prevent and mitigate the impact of LBGT communities in society. Based on the research that has been done using empirical law research method, it can be seen that the existence of this LGBT community does not conflict with the value of noble values of Pancasila. IntisariKeberadaan komunitas Lesbian, Gay, Biseksual, dan Transgender (LGBT) di Indonesia masih dilematis. Sebagian masyarakat memandang komunitas LGBT melanggar norma hukum, agama maupun kesusilaan. Namun, di lain pihak ada sebagian masyarakat yang menganggap komunitas LGBT adalah bagian yang tak terpisahkan dari masyarakat pada umumnya. Penelitian ini bertujuan memahami pandangan Pancasila terhadap keberadaan komunitas LGBT di Indonesia. Metode penelitian menggunakan metode hukum empiris. Hasil penelitian menunjukan bahwa keberadaan komunitas LGBT tidak bertentangan dengan nilai-nilai luhur Pancasila.